Studi Minat Beli di Belikopi Semarang - Hermawan Budiyanto (CiDEA Journal, 2024)
The aim of the study on buying interest at Belikopi was to determine: 1. The influence of price level on consumer buying interest in Belikopi Sampangan 2. The influence of brand image on consumer buying interest in Belikopi Sampangan 3. The influence of price level and brand image on consumer buying interest in Belikopi Sampangan. The type of research used is explanatory, namely research that explains the influence between variables and hypotheses. The test results show 1) there is a significant influence between Price Level and Buying Interest 2) there is a significant influence between Brand Image and Buying Interest d 3) there is a significant influence between Price Level and Brand Image together on Buying Interest 4) From The results of calculating the coefficient of determination obtained a result of 57.04% and the remaining 42.96% was influenced by other variables or factors. 1. Belikopi Sampangan must be able to adjust prices to product quality and maintain reasonable and affordable prices for customers, so as to increase buying interest consumer. 2. Belikopi Sampangan must continue to maintain a good reputation, trustworthy quality and positive perception and be able to overall meet consumer expectations.